(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article shares procedures for creating a digital library of dance movements entitled Espiral, which documents part of the dance technique of Brazilian artist Eva Schul (1948). Created using a motion capture system (mocap) and video recordings, it consists of twelve dance sequences, viewed through dancers performing the movements and their respective dancing avatars. The composition of the library allowed reflective thinking processes on the notion of the archive’s living potential, as well as understanding the movements that constitute it as atoms of dance and the video recordings as digital echoes of Eva Schul’s teaching.